The GATA transcription factor GNC plays an important role in photosynthesis and growth in poplar. (24th December 2019) - An, Yi; Zhou, Yangyan; Han, Xiao; Shen, Chao; Wang, Shu; Liu, Chao; Yin, Weilun; Xia, Xinli
Abstract : Thirty-nine GATA transcription factor genes were identified in the poplar genome. The GATA transcription factor PdGNC positively regulates photosynthesis and plant growth by promoting chloroplast development in poplar.  Abstract: GATA transcription factors are involved in the regulation of diverse growth processes and environmental responses in Arabidopsis and rice. In this study, we conducted a comprehensive bioinformatic survey of the GATA family in the woody perennial Populus trichocarpa . Thirty-nine Populus GATA genes were classified into four subfamilies based on gene structure and phylogenetic relationships. Predicted cis -elements suggested potential roles of poplar GATA genes in light, phytohormone, development, and stress responses. A poplar GATA gene, PdGATA19 / PdGNC (GATA nitrate-inducible carbon-metabolism-involved), was identified from a fast growing poplar clone. PdGNC expression was significantly up-regulated in leaves under both high (50 mM) and low (0.2 mM) nitrate concentrations. The CRISPR/Cas9-mediated mutant crispr-GNC showed severely retarded growth and enhanced secondary xylem differentiation. PdGNC -overexpressing transformants exhibited 25–30% faster growth, 20–28% higher biomass accumulation, and ~25% increase in chlorophyll content, photosynthetic rate, and plant height, compared with the wild type. Transcriptomic analysis showed that PdGNC was involved in photosynthetic electron transfer and carbon assimilation in the leaf, cell division and carbohydrate utilization in the stem, and nitrogen uptake in the root. These data indicated that PdGNC plays a crucial role in plant growth and is potentially useful in tree molecular breeding.